C-reactive protein is not a useful indicator for infection in surgical intensive care units - Cicarelli, Domingos Dias; Vieira, Joaquim Edson; Benseñor, Fábio Ely Martins (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: C-reactive protein (CRP) is commonly used as a marker for inflammatory states and for early identification of infection. This study aimed to investigate CRP as a marker for infection in patients with postoperative septic shock. DESIGN AND SETTING: Prospective, single-center study, developed in a surgical intensive care unit at Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: This study evaluated 54 patients in the postoperative period, of whom 29 had septic shock (SS group) and 25 had systemic inflammatory response syndrome (SIRS group). All of the patients were monitored over a seven-day period using the Sequential Organ Failure Assessment (SOFA) score and daily CRP and lactate measurements. RESULTS: The daily CRP measurements did not differ between the groups. There was no correlation between CRP and lactate levels and the SOFA score in the groups. We observed that the plasma CRP concentrations were high in almost all of the patients. The patients presented an inflammatory state postoperatively in response to surgical aggression. This could explain the elevated CRP measurements, regardless of whether the patient was infected or not. CONCLUSIONS: This study did not show any correlation between CRP and infection among patients with SIRS and septic shock during the early postoperative period.